2008
DOI: 10.1051/agro:2007058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compost enriched with N and L-tryptophan on soil and maize

Abstract: -Composting provides an excellent way to manage the huge volume of organic waste and convert it into a useful soil amendment. The effectiveness of composted organic waste can be further improved by enriching and blending it with nutrients and biologically active substances. The resulting value-added composts can be used at substantially low rates such as a few hundred kg per ha compared with conventional use of organic wastes in tons per ha. This approach could have practical significance in reducing the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 21 publications
3
41
0
1
Order By: Relevance
“…Furthermore, OM maintains the dynamics and productive potential of the "rhizosphere". Organic matter improves soil structure, increases water retention capacity, stimulates soil microbes, and provides nutrients (Fontaine et al, 2003;Ahmad et al, 2008a;2008b;Shahzad et al, 2008;Reid et al, 2011a;2011b). The supplementary effect of compost may also be attributed to better supply of the organic C and energy required by heterotrophs, consequently, more and efficient establishment of PGPR producing better results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, OM maintains the dynamics and productive potential of the "rhizosphere". Organic matter improves soil structure, increases water retention capacity, stimulates soil microbes, and provides nutrients (Fontaine et al, 2003;Ahmad et al, 2008a;2008b;Shahzad et al, 2008;Reid et al, 2011a;2011b). The supplementary effect of compost may also be attributed to better supply of the organic C and energy required by heterotrophs, consequently, more and efficient establishment of PGPR producing better results.…”
Section: Discussionmentioning
confidence: 99%
“…Organic waste materials were composted as described by Ahmad et al (2008a). From the composted organic waste materials, 50% PEC was prepared by enrichment with 50% of full dose of phosphatic fertilizer using single super phosphate (SSP) as the source of P while remaining 50% P was applied at the time of sowing.…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urea and ammonium sulphate fertilisers are available on the local market and popularly used by Ghanaian farmers. Ahmad et al (2008), Bangar et al (1989), Rao et al (2007), and Sridhar and Adeoye (2003) reported on the use of urea or ammonium sulphate to enrich compost to obtain a compost-fertiliser product. However, they did not address the effect of these two N sources (urea or ammonium sulphate) on the final N content of the compost-fertiliser product; the form(s) of urea or ammonium sulphate (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…dry, paste or liquid) that could blend best with co-compost and the effect of storage on the properties of the N-enriched co-compost. For instance, Ahmad et al (2008), Bangar et al (1989), Han et al (2004) and Sridhar and Adeoye (2003) used urea, whereas Rao et al (2007) used ammonium sulphate. Furthermore, Ahmad et al (2008), Rao et al (2007) and Sridhar and Adeoye (2003) applied the inorganic fertiliser in dry form, but Bangar et al (1989) and Han et al (2004) dissolved it in water.…”
Section: Introductionmentioning
confidence: 99%